ANALYSIS OF CRITICAL THINKING SKILLS AND COLLABORATION OF ELECTRONIC ENGINEERING EDUCATION STUDENTS IN ELECTRICAL MACHINERY COURSE - Prastyaningrum, Ihtiari; Imansari, Nurulita; Kholifah, Umi (Sanata Dharma University Yogyakarta, 2023)
The development of the 21st century is directed at the specialization of certain abilities. This certainly influences the goals of Indonesia's national education, where graduates must be equipped with 21st-century skills. These 21st-century skills we can call the 4Cs, namely critical thinking (critical thinking), collaboration (collaboration), creativity (creativity), and communication (communication). The ability to collaborate and think critically needs to be applied in the learning process, including in the Electrical Machinery course. In the Electrical Machines course, lectures are conducted using an electric machine trainer. The use of this trainer is intended to create a student-centered learning atmosphere. To analyze students' critical thinking and collaboration skills in the electrical machine course, we conducted a series of studies related to this. The research method used is a quantitative research method with a one-shot case study research design. From the research, it was found that learning activities using an electric machine trainer were able to optimize students' critical thinking skills. This is because learning using a trainer is student-centered learning, where students play an active role in the learning process. Besides being able to optimize student collaboration skills because the learning process is carried out in groups. Discussion activities carried out in groups provide experiences for students to develop collaboration skills.